The Impact of Armed Conflict in Northern Nigeria on Reproductive Autonomy and Unmet Need for Family Planning: A Difference‐in‐Differences Propensity Score Matching Approach - Lieke Vilier; Wim Groot (Health Science Reports)
ABSTRACT Background and Aims In Northern Nigeria, entrenched patriarchal norms, high maternal mortality rates, low contraceptive use, and a fragile healthcare system exacerbated by conflict pose significant challenges to reproductive autonomy and family planning. This study investigates the impact of conflict exposure on women's unmet family planning needs and reproductive autonomy, including contraceptive decision‐making, discussing condom use, and declining sexual advances. Methods This study employs a kernel‐based difference‐in‐differences model using data from the Nigerian Demographic and Health Survey (2008, 2013, 2018) linked with conflict incident data from the Armed Conflict Location and Events Database. Results Results suggest that conflict exposure is generally associated with women's reproductive autonomy, with effects varying over time and between urban and rural settings. Specifically, urban conflict exposure before 2013 was found to be associated with an increased ability for women to refuse sexual advances and a reduction in unmet family planning needs. Conflict exposure during 2014–2018 is found to be associated with an increased ability for women to request condom use and an increased ability to refuse sex. Conclusion The diverse outcomes, which predominantly show positive associations between conflict exposure and women's reproductive autonomy, may be attributed to the presence of humanitarian assistance, changed fertility preferences and altered gender norms during conflict.